Konsepsi Dan Tolok Ukur Ketahanan Regional - Prima Roza (Fakultas Seni Rupa dan Desain ITB, 2006)
The development of interaction among people is nowadays very much influenced by two contradictory factors. They are the unifying interest and tribalism. The later is not in a context of traditional anthropology. The fact can be seen from the trend of regionalism recently, particularly in the region of North America, Asia Pacific, and Europe. In the effort of balancing the competitive ability among the three regions, and in making them synergized, it is necessary to pay close attention to the formation of competitive supremacy from time to time. Besides that, since regionalisation involves a group of countries, each of which has each own national interest, it is necessary that the synergy effort has to be led to a balance on the similar element/feature, and not the effort of interest accumulation of each country member of a region. Within this context, this study is conducted with reference to the above mentioned principles, and it is focused mainly on the ASEAN region in which Indonesia is the most influencing country member. The study focuses on the current regionalisation development of the three main regions. Also, the study predicts the targets they intend to achieve by identifying the dominant parameters for the targets and correlates the parameters with the targets. In addition, the extrapolation towards the globally shared values into the concept of Indonesia's National Resillience is done. The extrapolation is done to enrich the concept of Indonesia's National Resillience, and the result of which can further be used to strengthen the regional resillience concept. This enriched regional resillience concept is then translated into quantitative parameter which are adopted as the indicators of the regional resillience concept.